Formulation and Evaluation of Halal Non-Aromatic Moisture and Protection Cream Preparations for Hajj and Umroh Pilgrims - Annisa, Rahmi; Anggraini, Wirda; Purwaningsih, Fauziyah Eni; Salsabila, Dhia Fadhilah; Samah, Moh.Alfin; Mutiah, Roihatul (Journal of Islamic Medicine, 2024)
Background: Protective moisturizer cream can be used by Hajj and Umrah pilgrims.They can use sunscreen moisturizer cream as a moisturizer and sunscreen to protect their skin from exposure to the sun because it does not contain alcohol or certain fragrances. Objective: This research aims to determine the halalness of ingredients, the presence or absence of aromatic content, the suitability of physical characteristics, and the effectiveness of the SPF value of halal non-aromatic Sunscreen moisturizer cream preparations using pre-experimental design research methods. Methods: The physical characteristics were evaluated, including organoleptic, homogeneity, spreadability, adhesive power, pH, and viscosity. Results: The organoleptic test results show that the Sunscreen moisturizer cream preparation has a yellowish-white color, is scentless, and has a soft texture. Homogeneity testing shows that this preparation is homogeneous. The spreadability test value of the preparation is 6.50 cm; the sticking power value is 3.77 seconds; the pH value is 5.00; the viscosity value is 5.64 cPs. The research results also show that the preparation contains halal ingredients and does not contain fragrances. Halal non-aromatic sunscreen moisturizer cream. Formula SPF value 38.332 ± 1.526 with ultra protection type. Conclusion: All evaluations of the physical characteristics of the Sunscreen moisturizer cream preparation have met the requirements for a good cream preparation, except for the viscosity test. It contains halal ingredients and has ultraprotective protection against UV light. Keyword : Cream, Sunscreen, Moisturizer, Non Aromatic, Hajj Care